The role of organizational commitment towards firm competitive advantage: a case study at Malaysia Rubber Board / Siti Nurfatihah Huzma Husham - Husham, Siti Nurfatihah Huzma (2015)
This research was conducted to carry out a study that entitled “The Role of Organization Commitment towards Firms Competitive Advantage among staff Malaysia Rubber Board. The purpose of this study is to investigate the relationship between three independent variables against one dependent variable. Basically, it consists of three factors that effect of firm competitive advantage among staff of Malaysia Rubber Board and the factors is Affective Commitment, Continuance Commitment, and Normative Commitment towards Firm Competitive Advantage. In order to complete this write up, few hypotheses were constructed and focused on the objectives to determine whether there is a significant relationship between affective commitment, continuance commitment, and normative commitment with firm’s competitive advantage. For this theses, 210 staff of Malaysia Rubber Board chosen as respondents for this study. The data was obtained from primary data by using questionnaire. All data collected through the questionnaire were analyzed systematically by Statistical Package for Social Science (SPSS). From the correlation testing, the result show three independent variables which are affective and continuance have a strong relationship, while normative commitment has a moderate relationship. For multiple regression analysis, the result indicate that Affective Commitment, Continuance Commitment and Normative Commitment are factors that affect firm’s competitive advantage among workers of Malaysia Rubber Board. In term hypothesis testing, two hypotheses pertaining to Affective Commitment, Continuance Commitment and Normative Commitment are accepted